MEDIA VIDEO ANIMASI SEBAGAI EDUKASI UNTUK MENINGKATKAN PENGETAHUAN IBU HAMIL TENTANG KEKURANGAN ENERGI KRONIK - Syafitri, Lini; Dewi, Vonny Khresna; Rusmilawaty, Rusmilawaty (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: High maternal mortality rates can occur due to complications during pregnancy and childbirth, one of which is Chronic Energy Deficiency (CED). Babirik Community Health Center targets 25% coverage of pregnant women with CED by 2024. Objective: One effort to improve the nutritional status of pregnant women is by increasing knowledge of mothers and families through animated videos. To find out the effect of animated videos on increasing the knowledge of pregnant women about CED at Babirik Health Center in 2025. Method: This study was a quasi-experimental study with a single-group pretest-posttest design. The study population consisted of 79 pregnant women, and a sample of 30 respondents was drawn using a purposive sampling technique. Data collection used a questionnaire. Data analysis used the Chi Square test. Result: Most pregnant women had insufficient knowledge before being given animated video media (12 mothers (40,0%), and after being given animated video media almost all of them had good knowledge (24 mothers (80,0%). There was an effect of providing animated videos on increasing pregnant women's knowledge about CED with a ρ value (0.038 < 0.05). Conclusion: Pregnant women are expected to be more active in seeking information about their health, both through electronic and other media.